The Blood Immune Cell Count, Immunoglobulin, Inflammatory Factor, and Milk Trace Element in Transition Cows and Calves Were Altered by Increasing the Dietary n-3 or n-6 Polyunsaturated Fatty Acid Levels - Sun, Xiaoge; Hou, Yuhuang; Wang, Yue; Guo, Cheng; Wang, Qianqian; Zhang, Yan; Yang, Zhantao; Wang, Zhonghan; Cao, Zhijun; Wang, Wei; Li, Shengli (Frontiers in Immunology, 2022)
Transition dairy cows experience sudden changes in both metabolic and immune functions, which leads to many diseases in postpartum cows. Therefore, it is crucial to monitor and guarantee the nutritional and healthy status of transition cows. The objective of this study was to determine the effect of diet enriched in n-3 or n-6 polyunsaturated fatty acid (PUFA) on colostrum composition and blood immune index of multiparous Holstein cows and neonatal calves during the transition period. Forty-five multiparous Holstein dairy cows at 240 d of pregnancy, were randomly assigned to receive 1 of 3 isoenergetic and isoprotein diets: 1) CON, hydrogenated fatty acid (control), 1% of hydrogenated fatty acid [diet dry matter (DM) basis] during pre- and postpartum, respectively; 2) HN3, 3.5% of extruding flaxseed (diet DM basis, n-3 PUFA source) during pre- and postpartum, respectively; 3) HN6, 8% of extruding soybeans (diet DM basis, C18:2n-6 PUFA source) during pre- and postpartum, respectively. Diets containing n-3 and n-6 PUFA sources decreased colostrum immunoglobulin G concentration but did not significantly change the colostrum IgG yield, compared with CON. The commercial milk yield was higher in the HN3 and HN6 than in the CON. Furthermore, the n-3 PUFA source increased neutrophil cell counts during the prepartum period and increased neutrophil percentage during the postpartum period when compared with control treatment. Diets containing supplemental n-3 PUFA decreased the serum concentration of IL-1β in maternal cows compared with control and n-6 PUFA during prepartum and postpartum. In addition, the neonatal calves serum concentration of TNF-α was decreased in HN3 compared with the HN6 treatment. The diet with the n-3 PUFA source could potentially increase the capacity of neutrophils to kill phagocytose and destroy pathogens in maternal cows by increasing the neutrophils numbers and percentage during the transition period. Meanwhile, the diet with n-3 PUFA source could alleviate the inflammation of maternal cows during the transition period and decrease the content of cytokines TNF-α of neonatal calves' inflammatory. It suggested that the highest milk production in n-3 PUFA treatment may partially be due to these beneficial alterations.